Assessment of the Flow at the Chatara on Koshi River Basin using Semi Distributed Model - Gautam, Narayan Prasad (Journal of the Institute of Engineering, 2017)
Hydrological modeling is a physical phenomenon to incorporate rainfall-runoff process in watershed area at particular point and analysis the behaviors of the flow through outlet. There are various types of models such as black box, conceptual and physical based model depends upon the availability of required data, parameters and description of the physical process. Semi distributed model is a conceptual and physical based model which has been developed to bridge the gap between the lumped and distributed model. It have more advantages than other models with respect to time of calculation, less number of parameters, comparatively low calibration needs and have high efficiency of model. The model performance may be achieved upon the qualitative and quantitative available rainfall data, land use data and size of the watershed. In this study, Koshi river basin was taken for the study area. Kinematic wave method was used for overland routing and Muskingum conge method was applied for channel routing to describe the discharge on Saptakoshi river and peak flow attenuation and dispersion observed in the direct runoff hydrograph. From this study result, Annual runoff, Peak flow and time of peak at the outlet are similar to the observed flow in calibration and verification period using trapezoidal channel. The nash efficiency obtained from the semi distributed model with kinematic wave method is more than 90%in verification periods and nearly 90% in calibration periods Hence Hydrological modeling is a powerful technique in the planning and development of integrated approach for management of water resources. Journal of the Institute of Engineering, 2016, 12(1): 184-198